Performance of Fractional Rate STBCcodes in Wireless Communications - Ghai, Meenakshi (My University, 2007)
Challenges in modern wireless communication are high data rate, reduction of data transmission cost per bit etc. To overcome the low data rate problems in 3 G, spacetime block coding is proposed in 4G. Space–time block coding, which is a new paradigm for transmitting data over fading channels using multiple transmit antennas. In implementing space time block coding, data is encoded using a space–time block code and the encoded data is split into MT streams which are simultaneously transmitted using MR transmit antennas. The received signal at each receive antenna is a linear superposition of the MT transmitted signals perturbed by noise. Maximum likelihood decoding is achieved in a simple way through decoupling of the signals transmitted from different antennas rather than joint detection. This uses the orthogonal structure of the space–time block code and gives a maximum-likelihood decoding algorithm, which is based only on linear processing at the receiver. Space–time block codes can be designed to achieve the maximum diversity order for a given number of transmit and receive antennas subject to the constraint of having a simple decoding algorithm. These codes achieve the maximum possible transmission rate for any number of transmit antennas using any arbitrary real constellation such as PAM. For an arbitrary complex constellation such as PSK and QAM, space–time block codes can be designed that achieve 1/2 of the maximum possible transmission rate for any number of transmit antennas. For the specific cases of two, three, and four transmit antennas, space–time block codes are designed that achieve, respectively, all, or 3/4 of maximum possible transmission rate using arbitrary complex constellations. In this thesis rate 1 by 2 and rate 3 by 4 systems are studied under different fading environments using different modulations and their performances are compared. Finally, performance of different rate schemes using three and four number of transmit antennas is compared. The rate 3 by 4 code and rate 1 by 2 code for three and four antennas outperform rate 1 code using two transmit antennas. The performance gain is less as compared to the pervious case when numbers of receive antennas is increased.
Keywords: Wireless Communication; Fractional Rate STBC Codes; Space Time Block Coding; Rayleigh Fading Channel Model